2009
DOI: 10.3748/wjg.15.3916
|View full text |Cite
|
Sign up to set email alerts
|

Soluble intercellular adhesion molecule-1, D-lactate and diamine oxidase in patients with inflammatory bowel disease

Abstract: AIM:To study the levels of serum soluble intercellular adhesion molecule-1 (sICAM-1), plasma D-lactate and diamine oxidase (DAO) in patients with inflammatory bowel disease (IBD), and the potential clinical significance. METHODS:Sixty-nine patients with IBD and 30 healthy controls were included in this study. The concentration of sICAM-1 was detected with enzyme-linked immunosorbent assay, the level of D-lactate and DAO was measured by spectroscopic analysis, and the number of white blood cells (WBC) was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 13 publications
(13 reference statements)
2
52
0
1
Order By: Relevance
“…S2) showed poor changes on expression of zonula occluden 1 (ZO1) and occludin proteins between the GM and NM groups. Close attention has been paid to the relationship between the changes in intestinal permeability and the development of disease, and it was reported that animals with inflammatory bowel disease (IBD) showed higher levels of serum DAO than healthy controls33. However, this experiment showed that there were no unintended effects on intestinal permeability due to the feeding of Cry2A rice.…”
Section: Resultsmentioning
confidence: 80%
“…S2) showed poor changes on expression of zonula occluden 1 (ZO1) and occludin proteins between the GM and NM groups. Close attention has been paid to the relationship between the changes in intestinal permeability and the development of disease, and it was reported that animals with inflammatory bowel disease (IBD) showed higher levels of serum DAO than healthy controls33. However, this experiment showed that there were no unintended effects on intestinal permeability due to the feeding of Cry2A rice.…”
Section: Resultsmentioning
confidence: 80%
“…Another study, however, found a significant increase of D-lactate in hospitalised patients with active IBD [6]. This difference may be explained by the fact that the patients we have included were in remission.…”
Section: Discussionmentioning
confidence: 77%
“…Diamine oxidase is primarily located to the small intestinal villi. When the small intestinal mucosa is damaged, increased intestinal permeability allows diamine oxidase to diffuse into blood, resulting in elevated serum diamine oxidase content . Serum d ‐lactate is another marker of gut barrier function, derived from the metabolism of intestinal indigenous flora.…”
Section: Discussionmentioning
confidence: 99%